2008
DOI: 10.1021/np800131f
|View full text |Cite
|
Sign up to set email alerts
|

Phytoecdysteroids from Ajuga macrosperma var. breviflora Roots

Abstract: Three new phytoecdysteroids, ajugacetalsterones C (1) and D (3) and breviflorasterone (2), were isolated from the roots of Ajuga macrosperma var. breviflora along with five known compounds, namely, 20-hydroxyecdysone, cyasterone, makisterone A, 20-hydroxyecdysone 3-acetate, and 20-hydroxyecdysone 2-acetate. The structures of 1-3 were elucidated on the basis of extensive 1D and 2D NMR spectroscopic studies. The new compounds possess acetal oxygen bridges between C-26 and C-20/C-22, or C-26/C-23, or a lactone br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 14 publications
(16 reference statements)
0
26
0
Order By: Relevance
“…1). 3,34 For the ecdysteroid extraction, a previously optimized protocol 38 was followed with some modications. 34 In brief, powdered plant material ($500 mg) was extracted rst with 10 ml of methanol (MeOH) two times and then the residue was extracted again with 85% MeOH and both fractions (100% MeOH and 85% MeOH) were mixed and dried.…”
Section: Extraction Of Ecdysteroidsmentioning
confidence: 99%
“…1). 3,34 For the ecdysteroid extraction, a previously optimized protocol 38 was followed with some modications. 34 In brief, powdered plant material ($500 mg) was extracted rst with 10 ml of methanol (MeOH) two times and then the residue was extracted again with 85% MeOH and both fractions (100% MeOH and 85% MeOH) were mixed and dried.…”
Section: Extraction Of Ecdysteroidsmentioning
confidence: 99%
“…Characteristic components of these genera are neoclerodane diterpenoids, 4,5 representative of an important chemical class with a variety of demonstrated biological activities including cytotoxic, analgesic, and antimicrobial activities. 69 The roots of J. columba , T. capillipes , and T. sagittata containing columbin ( 1 ) have been used in folk medicine as analgesic and antipyretic agents. 2 Tinospora sagittata , which is in the Pharmacopeia of the People’s Republic of China , demonstrates anti-inflammatory, analgesic, antibacterial, antiulcer, antitumor, and antistress effects, 10–13 and its roots have been used in traditional medicine to ease sore throats, stop diarrhea, and treat upper respiratory tract infections.…”
mentioning
confidence: 99%
“…Similarly, larvae of the greenhouse whitefly ( Trialeurodes vaporariorum ) exhibited 100% mortality when fed on Ajuga reptans plants. High levels of the three major phytoecdysteroids, 20-hydroxyecdysone (ecdysterone), makisterone A and cyasterone, have been found in several plants, including Ajuga [ 4 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], quinoa and spinach [ 4 , 27 ]. An extract of 20-hydroxyecdysone and cyasterone from Ajuga iva L. showed high activity against Oligonychus perseae [ 28 , 29 ]; a dose of 5 μg/mL of pure extracted A. iva ecdysterone significantly reduced fecundity, fertility and survival of this pest, while commercial 20-hydroxyecdysone at the same dose had lesser effects [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clerodanes (diterpenoids) are a large group of C20 terpene compounds derived from geranylgeranyl diphosphate and biosynthesized through the deoxyxylulose phosphate pathway in the cytoplasm, mostly in the leaves and stems of the Lamiaceae and Asteraceae families [ 31 ]. Clerodin was originally isolated from Clerodendrum infortunatum (Lamiaceae), and has potential as a natural pesticide due to its insect repellent activities [ 20 , 32 , 33 , 34 ]. Koul [ 33 ] showed that the most active compounds, dihydroclerodin and clerodin hemiacetal from Caryopteris divaricata , exhibit 100% antifeedant activity at 50 ppm.…”
Section: Introductionmentioning
confidence: 99%